Occurrence of white spot syndrome virus and Vibrio parahaemolyticus in brackishwater shrimp culture systems of Sundarban, West Bengal, India - Das, Sanjoy; Ghoshal, Tapas Kumar; Biswas, Gouranga (Indian Journal of Fisheries, 2018)
White spot disease (WSD) and acute hepatopancreatic necrosis disease (AHPND) are two important and highly fatal diseases of cultured shrimps. The occurrence of white spot syndrome virus (WSSV) was found to be very high in brackishwater aquaculture systems of Sundarban area in West Bengal, with 40.6% of the samples being positive of which 18.75% being positive in the first step PCR. The prevalence of WSSV in traditional and semi-intensive culture systems was found as 59.3 and 27%, respectively. On the other hand, presence of Vibrio parahaemolyticus was detected in 53.1, 55.5 and 75.9% of the shrimp, water and soil samples, respectively. All the isolates of V. parahaemolyticus contained toxR gene as detected by PCR. However, none of the isolates was realised as AHPND causing isolate by PCR. Moreover, tdh gene, which causes gastroenteritis in human beings, was also not detected in any of the isolates. The present study indicated that WSSV is the major cause of crop failure in the brackishwater shrimp culture systems of Sundarban, India. Although, V. parahaemolyticus is highly prevalent in brackishwater shrimp culture systems of Sundarban, strains causing gastroenteritis or AHPND were not detected during the present study.